Conversion to Islam in Malaysia : antecedents, consequences and moderating variables - Shikongo, Armas Eliputse Etutala (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The general objective of this study was to investigate individual religious conversion, specifically, conversion to Islam: an important academic area that seems to be currently under-investigated in Malaysia. The study focused on pre- and post-conversion to Islam experiences. The key variables of the study were general life dissatisfaction, general life satisfaction, truth search, truth discovery, negative experiences, attractiveness of Islam, commitment to Islam, demographic factors and personality factors. The sample consisted of 161 converts to Islam in the state of Selangor, Malaysia. Data were collected using self-tailored questionnaires in English and Malay. The sample was selected through convenience and snowballing sampling techniques. Using SPSS version 16.1 for Windows, descriptive and inferential statistics were computed. Results support the correlation hypotheses partially. There were significant correlations between some of the key variables. The study has made unique contributions to knowledge in terms of theory, method and applied psychology. The findings of this study have important implications for psychological practice, with specific reference to clinical and counselling psychology. The results highlight a unique need to conceptualise and develop a post-conversion to Islam therapeutic approach to help new Muslims to better cope with their pre- and post-religious conversion experiences. Religious conversion or faith-based lifestyle change has been found to be one of the most psycho-socially challenging experiences that need professional attention, especially in terms of adjustment to a new way of life.